1953
DOI: 10.1079/bjn19530033
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritive Value of Colostrum for the Calf

Abstract: The nutritional importance of lecithin for newborn animals has been demonstrated in America. Esh, Sutton, Hibbs & Krauss (1948) compared the performance of calves receiving colostrum for the first 7 days of life with that of calves deprived of colostrum but given skim milk containing a daily supplement of 25,000-37,500 i.u. vitamin A, and with that of calves that received in addition 3-4'5 g of soya-bean lecithin. Three of the five calves given the vitamin A supplement died within the first I I days of life, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1955
1955
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The ZST test is the most widely used and highly accepted method for quantifying the specific immunoglobulin levels to determine the IM activity of test drugs. In the present study, the ZST test was modified to determine the correlation between the concentration of specific immune globulins present in the serum and the intensity of the ZST reaction that developed [ 11 , 12 ]. The findings clearly showed that pretreatment with various doses of IM-133N (125, 250, 500 and 1,000 mg/kg, p.o.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ZST test is the most widely used and highly accepted method for quantifying the specific immunoglobulin levels to determine the IM activity of test drugs. In the present study, the ZST test was modified to determine the correlation between the concentration of specific immune globulins present in the serum and the intensity of the ZST reaction that developed [ 11 , 12 ]. The findings clearly showed that pretreatment with various doses of IM-133N (125, 250, 500 and 1,000 mg/kg, p.o.)…”
Section: Discussionmentioning
confidence: 99%
“…In the first set of experiments, the strength of Escherichia coli ( E. coli ) required for inducing abdominal sepsis and 100% mortality was established, and based on the results, the effect IM- 133N against E. coli induced abdominal sepsis and mortality was evaluated in the second set of experiments. In the first set, a pathogenic strain of E. coli was subcultured in a nutrient broth by using a shaker water bath at 37°C, and the total viable-cell count was observed from the MacConkey agar plates [ 11 , 12 ]. Different doses of E. coli were administered intraperitoneally to different groups of animals to elucidate the dose of viable E. coli cells required to cause abdominal sepsis with 100% mortality within 48 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of this protection has been the object of much study and it is now well established that protection is due to the presence of immunoglobulins in the colostral whey (Aschaffenburg et al 1951). Only when calves are fed either whey or the extracted immunoglobulins are they protected.…”
Section: Introductionmentioning
confidence: 98%